The inland aquaculture innovation technology development in Cambodia - Kong, Heng; Tuy, Sinak; Kongkroy, Chay; Sithirith, Mak; Sean, Vichet; Sok, Sao (Inland Fisheries Research and Development Institute, 2024)
The development of inland aquaculture in Cambodia has evolved significantly, focusing on freshwater systems like ponds, cages, and rice-fish integration. Aquaculture contributes 40.7% of fisheries production, addressing rising fish demand amid capture fishery declines. Challenges include poor seed quality, feed reliance on imports, and limited technical expertise. Innovations like plastic tanks, aquaponics, and climate-resilient practices show promise. The value chain remains underdeveloped, with low sanitary standards and limited infrastructure. Future growth requires investment in technology, regulatory frameworks, and sustainable practices. Supporting local hatcheries, promoting efficient feed use, and mitigating climate impacts are crucial for scaling aquaculture sustainably.